BENTUK DAN MAMFAAT NILAI PENDIDIKAN FOKLOR BALI - Putera Semadi, Anak Agung Gde (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2019)
AbstractGenerally folklore could be described as myths, legends, music, oral history, proved, jokes, superstitions, fables, and power which include traditions in a subcultural culture, or a group of fochlores are a set of practices which become means of spreading various cultural traditions. Bali fochlor as a variety of forms which relatively have same characteristic. There are oral, partialy oral, and not oral folklores. The socio-cultural values in folklore which full of purpose of life are having enormous benefits as good character guides for every child of our nation. Therefore, this research was completed on time.This research was designed as a part of the phenomenologycal approach. The object of the study was on a text and its context in a community, and this research did not use the hypothesis. Analysis descriptive method and analysis content which were strengthened by the paradigm of literary sociology as its theoretical study were the method used in describing the result of its data processed.From a more comprehensive poin of view, this research is not only useful for improving the means of language, literature, and Balinese script learning, but more important than that is as a means of social controler in order to create a harmonious and peaceful atmosphere. Key words: Forms, Educational values, and Fochlor benefits. Abstrak Secara umum foklor meliputi mite, legenda, musik, sejarah lisan, pepatah, lelucon, takhyul, fabel, dan kekuasaan yang meliputi tradisi dalam suatu budaya subkultur, atau kelompok foklor merupakan serangkaian praktik yang menjadi sarana penyebaran berbagai tradisi budaya. Foklor Bali memiliki bentuk beragam dengan sifat atau ciri-ciri yang relatif sama. Ada foklor lisan, sebagian lisan, dan bukan lisan. Nilai-nilai sosial budaya dalam foklor yang sarat dengan tujuan hidup dan kehidupan memiliki mamfaat yang sangat besar sebagai penuntun karakter yang baik bagi setiap anak bangsa. Oleh karena itu, maka penelitian ini diselesaikan tepat pada waktunya. Penelitian ini dirancang sebagai bagian dari pendekatan penomenologis. Objek kajiannya pada teks serta konteksnya yang ada di masyarakat, dan tidak menggunakan hipotesis. Dalam menguraikan hasil pengolahan data digunakan metode deskritif analisis dan konten analisis serta diperkuat dengan paradigma sosiologi sastra sebagai kajian teoritisnya. Dari sudut pandang yang lebih komprehensif penelitian ini tidak sekadar bermamfaat bagi peningkatan media pembelajaran bahasa, sastra, dan aksara Bali, tetapi lebih penting dari itu adalah sebagai sarana pengendali sosial dalam rangka menciptakan suasana rukun, tenteram, dan damai. Kata kunci: Bentuk, Nilai pendidikan, dan Manfaat foklor.